The sex offender housing dilemma: community activism, safety, and social justice - Williams, Monica (New York University Press, 2018)
The production of siting conflicts over SVP placements -- Political mobilization in countrified suburbia -- Litigating in a rural outpost -- Politics, litigation, and disorganization in an urban city -- The local context of community opposition to SVP placements -- Solving the sex offender housing dilemma -- Acknowledgments -- Appendix: selecting cases, gaining access, and collecting data in three communities